2019
DOI: 10.1155/2019/9641945
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Melanoma as Acute Mastoiditis in a 10-Month-Old Female Child

Abstract: We present a rare case of transplacental-transmitted maternal melanoma to the placenta and foetus during the pregnancy of a 34-year-old woman. She was diagnosed with a melanoma at the age of 25, for which she was treated with chemotherapy. During her pregnancy, she presented with a recurrence of the disease and died 3 months after delivery. The 10-month-old female child presented with a recurrent retroauricular oedema on the left side. A trephination of mastoid apophysis followed. Multiple fragments of dark-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Twenty-three publications were based on a pooled total of 24 children (<18 years old) with diseases mimicking AM ( Table 2 ). 3,4,8-28 Age ranged from 10 weeks to 16 years with a male predominance (14 males, 8 females, 2 not reported). In total, 11 unique diseases were cited: acute myelogenous leukemia (AML), angiosarcoma, cranial fasciitis, Ewing sarcoma, Kawasaki disease, Langerhans cell histiocytosis (LCH), liposarcoma, melanoma, non-Hodgkin B- and T-cell lymphoma (NHL), and RMS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-three publications were based on a pooled total of 24 children (<18 years old) with diseases mimicking AM ( Table 2 ). 3,4,8-28 Age ranged from 10 weeks to 16 years with a male predominance (14 males, 8 females, 2 not reported). In total, 11 unique diseases were cited: acute myelogenous leukemia (AML), angiosarcoma, cranial fasciitis, Ewing sarcoma, Kawasaki disease, Langerhans cell histiocytosis (LCH), liposarcoma, melanoma, non-Hodgkin B- and T-cell lymphoma (NHL), and RMS.…”
Section: Resultsmentioning
confidence: 99%
“…Further history revealed that the girl’s mother died from melanoma when the girl was 3 months old; therefore, her melanoma likely represented fetal metastasis. Her disease underwent spontaneous regression, and she remained disease free at 4‐year follow‐up 22 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We selected 8 cases from 10 articles (two articles described the same cases) reporting transplacental transmission of melanoma, which are summarized in Table S5. [280][281][282][283][284][285][286][287][288][289] The mean age at diagnosis was 5.3 months (range: 0.37-10), six were males, most of them presenting multiple localisations of melanoma metastasis at diagnosis. The number of melanoma-related deaths was 5, and three patients underwent spontaneous regression.…”
Section: Transplacental Melanomamentioning
confidence: 99%
“…These malignancies can erode through the temporal bone, inducing cranial nerve (CN) impairment, hearing loss, vertigo, or otalgia (8). Because of the rarity, insidious nature, and nonspecific presentation of temporal bone MM, patients may experience delays in diagnosis and treatment, as this condition may be initially misdiagnosed as serous otitis media or otomastoiditis (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%